MODERN STRATEGIES IN THE MANAGEMENT OF CARDIOGENIC SHOCK: FROM MECHANICAL CIRCULATORY SUPPORT TO AI‑BASED MONITORING - Paulina Frączkiewicz; Patryk Brzezicki; Izabela Harpula; Radosław Ramotowski; Justyna Bogdan; Benedykt Baljon; Natalia Bębenek; Gabriela Barszcz; Monika Błądek; Karolina Drygała; Sylwia Wit (International Journal of Innovative Technologies in Social Science, 2025)
Background and objective: cardiogenic shock (CS) remains a leading cause of mortality in acute myocardial infarction and other cardiac conditions. Traditional medical therapy and early mechanical devices have limitations in survival and organ perfusion. Recent advances in mechanical circulatory support (MCS) devices and the integration of AI-based hemodynamic monitoring may offer improvements. This review aims to summarize modern strategies in managing cardiogenic shock, focusing on MCS (ECMO, Impella, LVAD) and AI-enabled monitoring tools, and to assess their efficacy, safety, and future potential. Scope of review: We reviewed literature published between 2020 and 2025, identified via PubMed, Scopus, and Web of Science. Included were observational studies, meta-analyses and randomized trials comparing types of mechanical circulatory support, assessing timing, outcomes (mortality, complications), and studies exploring AI or digital monitoring in the CS setting. Findings: recent meta-analyses suggest that Impella support is associated with lower in-hospital mortality, fewer bleeding and stroke events compared to VA-ECMO in some cohorts, though long-term survival differences are less clear (e.g. Impella vs ECMO meta-analyses). Early MCS initiation appears to improve outcomes. AI and digital monitoring remain less well studied in CS, but editorials and early studies indicate potential for better patient selection, real-time adjustments, and prediction of deterioration. Conclusions: modern CS management increasingly combines mechanical support with improved timing, device selection, and may benefit from AI-driven monitoring tools. However, high-quality randomized trials are still required, especially those integrating AI monitoring. Future research should address standardization of monitoring protocols, cost-effectiveness, and outcome measures beyond mortality.